Simultaneous observations of a low-altitude ion upflow by the EISCAT radar and molecular ions in the ring current by the Arase (ERG) satellite - Takada, Masayoshi; Seki, Kanako; Ogawa, Yasunobu; Keika, Kunihiro; Kasahara, Satoshi; Yokota, Shoichiro; Hori, Tomoaki; Asamura, Kazushi; Miyoshi, Yoshizumi; Shinohara, Iku (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences, Wed. 2 Dec. conference object